Remediation of Methyl Red Dye from Aqueous Solutions by Using Biosorbents Developed from Floral Waste - Abdelfattah Amari; Virendra Kumar Yadav; Sabir Khan Pathan; Bijendra Singh; Haitham Osman; Nisha Choudhary; Khaled Mohamed Khedher; Anup Basnet (Adsorption Science & Technology)
The disposal of biological waste into water bodies is a major global concern as it leads to water pollution resulting in the loss of plenty of revenue in the cleaning of water bodies. Here, in the present research work, sacred flowers were collected, segregated, sun-dried, and powdered. The dried floral powders (marigold and rose) were characterized by field emission scanning electron microscopy (FESEM), electron diffraction spectroscopy (EDS), Fourier transforms infrared spectroscopy (FT-IR), and X-ray diffraction (XRD). The microscopy revealed the irregular spherical shape of the sheet-like structure whose size varies in microns. The EDS revealed the elemental composition which was dominated by mainly carbon and oxygen. The XRD shows the presence of carbon (10-25ɵ) in the amorphous form and the absence of any crystalline phase in the biosorbents. The FT-IR showed peaks that conformed to the presence of functional groups like -OH and a carbonyl group. The dried powders were used as an economical and eco-friendly biosorbent for the removal of methyl red (MR) dye from the aqueous solutions by batch adsorption study. After 60 minutes of contact time, the marigold powder (MGP) and rose petal powder (RPP) showed decolorization of 61.16% and 56.08% for 2 ppm of MR dye. The kinetic revealed that the dye removal reaction does not follow the pseudo-first-order as well as the pseudo-second-order. The utilization of such waste-based biosorbents will minimize solid waste and also will provide an economical biosorbent for the removal of environmental pollutants.